2015
DOI: 10.1182/blood-2015-04-643148
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of quinine-dependent monoclonal antibody binding to platelet glycoprotein IIb/IIIa

Abstract: Key Points Drug-induced modulation of antibody specificity appears to explain the binding of drug-dependent mAbs to αIIb/β3 integrin. Drug-dependent platelet antibodies differ greatly from classic hapten-specific antibodies and may be induced by a quite different mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…Quinine has been commonly studied to understand the molecular mechanisms of drug-dependent antibody formation [31][32][33]. Quinine-dependent antibodies may be derived from a pool of naturally-occurring antibodies that are weakly reactive with autologous proteins [31,33].…”
Section: Nonementioning
confidence: 99%
See 1 more Smart Citation
“…Quinine has been commonly studied to understand the molecular mechanisms of drug-dependent antibody formation [31][32][33]. Quinine-dependent antibodies may be derived from a pool of naturally-occurring antibodies that are weakly reactive with autologous proteins [31,33].…”
Section: Nonementioning
confidence: 99%
“…Quinine-dependent antibodies may be derived from a pool of naturally-occurring antibodies that are weakly reactive with autologous proteins [31,33]. Quinine may have unique amphipathic properties that allow it to become integrated into complementaritydetermining regions of naturally occurring antibodies, creating a hybrid paratope that greatly increases binding affinity to cell surface antigens [32].…”
Section: Nonementioning
confidence: 99%
“…1,2 I n DITP, a drug somehow induces a tight interaction of antibody with one's own platelet antigen, leading to drug-dependent depletion of platelets. 3 In the absence of the drug, the antibody does not bind to the platelet with sufficient affinity to cause pathological damage.…”
Section: Renhao LI Emory University School Of Medicinementioning
confidence: 99%
“…The quinine-induced conformational change appears to be the molecular basis for the quinine-facilitated binding of 314 antibodies, as Bougie et al reported that the binding affinity of 314.1 antibody for purified integrin a IIb b 3 in the presence of quinine was 5 times tighter than that in the absence of quinine. 2 The quinine/314-antibody structures also point to an interesting possibility regarding the origin of drug-dependent antibodies; quinine may fit, perhaps by chance, into a preexisting antibody to either greatly improve its affinity for a platelet antigen or enable its recognition of a different antigen. Bougie et al 2 reported that 314.1 antibody with quinine bound 2 copies of a IIb b 3 on the platelet, as its apparent affinity for the platelet was orders of magnitude higher than that for the purified monovalent a IIb b 3 .…”
Section: Renhao LI Emory University School Of Medicinementioning
confidence: 99%
“…Various in vitro assays have been developed to assess the risk of mAb drug-mediated thrombocytopenia. One of the commonly used methods is measuring direct binding of the mAb drugs in platelets by flow cytometry, surface plasmon resonance (SPR), or ELISA (Bougie, Peterson, Rasmussen, & Aster, 2015;Santostefano et al, 2012). A mAb drug candidate that can bind to platelets is generally expected to increase the risk of platelet phagocytosis through recognition of either the bound drug itself (if the drug contains an effective Fc portion) and/or via anti-drug antibodies that can potentially develop in vivo.…”
mentioning
confidence: 99%